The Lever of Riches : Technological Creativity and Economic Progress. - Mokyr, Joel (Oxford University Press, USA, 1990)
In a world of supercomputers, genetic engineering, and fiber optics, technological creativity is ever more the key to economic success. But why are some nations more creative than others, and why do some highly innovative societies--such as ancient China, or Britain in the industrial revolution--pass into stagnation? Beginning with a fascinating, concise history of technological progress, Mokyr sets the background for his analysis by tracing the major inventions and innovations that have transformed society since ancient Greece and Rome. What emerges from this survey is often surprising: the c.